2008
DOI: 10.1029/2007pa001459
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for major environmental perturbation prior to and during the Toarcian (Early Jurassic) oceanic anoxic event from the Lusitanian Basin, Portugal

Abstract: [1] The timing and causal relationships between the pronounced negative C isotope excursion and paleoenvironmental perturbations associated with the Toarcian oceanic anoxic event (Early Jurassic) remain unclear, particularly because biotic crises and carbonate production decrease appear to have been initiated earlier than the main C isotope anomaly. Here we present a new quantification of Late Pliensbachian-Early Toarcian calcareous nannofossils abundance and size from the Peniche reference section (Portugal) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
259
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(286 citation statements)
references
References 68 publications
(202 reference statements)
24
259
0
3
Order By: Relevance
“…The latter value is somewhat similar to the recent estimate by Suan et al (2008), who assigned a value of 600 kyr for the duration of the T-OAE negative excursion in the Lusitanian Basin. Suan et al (2008) further suggested that the entire excursion (negative and positive excursion) lasted 900 kyr. If the end of the T-OAE excursion at Katsuyama is taken to occur between ca.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The latter value is somewhat similar to the recent estimate by Suan et al (2008), who assigned a value of 600 kyr for the duration of the T-OAE negative excursion in the Lusitanian Basin. Suan et al (2008) further suggested that the entire excursion (negative and positive excursion) lasted 900 kyr. If the end of the T-OAE excursion at Katsuyama is taken to occur between ca.…”
Section: Resultssupporting
confidence: 90%
“…5) represents the excursion found in European sections at the Pliensbachian/Toarcian boundary. Evidence for a Pliensbachian/Toarcian negative CIE from Europe has been documented from sections in Yorkshire (Littler et al, 2009) and Peniche (Hesselbo et al, 2007;Suan et al, 2008) and is also apparent in the Mochras Farm record of Wales (Jenkyns et al, 2001) (Fig. 6).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Especially relevant are the latest Pliensbachian−Early Toarcian climate changes, which have been documented in many sections from Western Europe (i. e. Saelen et al, 1996;McArthur et al, 2000;Röhl et al, 2001;Schmidt-Röhl et al, 2002;Bailey et al, 2003;Jenkyns, 2003;Rosales et al, 2004;Gómez et al, 2008;Metodiev and Koleva-Rekalova, 2008;Suan et al, 2008Suan et al, , 2010Dera et al, 2009Dera et al, , 2010Dera et al, , 2011Gómez and Arias, 2010;García Joral et al, 2011;Gómez and Goy, 2011;Fraguas et al, 2012), as well as in Northern Siberia and in the Artic Region (Zakharov et al, 2006;Nikitenko, 2008;Suan et al, 2011). The close correlation between the severe Late Pliensbachian Cooling and the Early Toarcian Warming events, and the major Early Toarcian mass extinction indi- cates that warming was one of the main causes of this faunal turnover (Kemp et al, 2005;Gómez et al, 2008;Gómez and Arias, 2010;García Joral et al, 2011;Gómez and Goy, 2011;Fraguas et al, 2012;Clémence, 2014;Clémence et al, 2015;Baeza-Carratalá et al, 2015).…”
Section: Introductionmentioning
confidence: 99%